HPV detection using primers MY09/MY11 and GP5+/GP6+ in patients with cytologic and/or colposcopic changes - Emanuella Meneses Venceslau; Mauro Muniz Bezerra; Anna Carolina Mota Lopes; Érick Vieira Souza; Alexandre Sherlley Casimiro Onofre; Claudia Moura de Melo; Verônica de Lourdes Sierpe Jeraldo; Fabiana Botelho de Miranda Onofre (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Cervical cancer is one of the most common diseases among women, and cause considerable morbidity and mortality. Considering that cervical cancer is an important neoplasia in northeastern Brazil, and the prevalence of high-risk human papillomavirus (HPV) is directly associated with it, this work had aimed to correlate the cytological and/or colposcopic findings with HPV infection status, and verify the performance of MY09/MY11 and GP5+/6+ primers for HPV detection. Material and method: Patients in this study were from Penedo-AL, a city with high level of poverty (poverty rate of 60.62%). Out of 70 patients with cytological and/or colposcopic changes, 32 agreed to participate in the study. Results: Regarding cytology, 21 (30%) patients presented atypical squamous cells of undetermined significance (ASC-US); 20 (29%), atypical glandular cells of undetermined significance (AGUS); 12 (17%), low-grade intraepithelial lesion (LSIL); five (7%), high-grade intraepithelial lesion (HSIL); and 12 (17%), positive colposcopy. From these, 27 (84%) presented the band gene encoding for human ß-globin. From the 27 patients, eight (30%) were positive for HPV. The results showed that the deoxyribonucleic acid (DNA) of HPV was detected in 15% and 30% by using MY-PCR and GP +-PCR, respectively. Conclusion: This study suggests that more than one type of oligonucleotide primer should be used in clinical samples to increase sensitivity for the detection of HPV.